Nucleoside alkaloids with anti-platelet aggregation activity from the rhizomes of Ligusticum striatum. Issue 10 (19th May 2019) - Pu, Zhong-Hui; Liu, Juan; Peng, Cheng; Luo, Min; Zhou, Qin-Mei; Xie, Xiao-Fang; Chen, Ming-Hua; Xiong, Liang
Abstract: Two new (1 –2 ) and six known (3 –8 ) nucleoside alkaloids were isolated from the rhizomes of Ligusticum striatum DC. Compounds1 and2 (liguadenosines A and B) were unusual N-10 substituted adenosine derivatives. Their structures were elucidated by extensive spectroscopic analyses and ECD calculation. Most of them significantly inhibited the abnormal increase in platelet aggregation induced by ADP at concentrations of 50 and 100 μM. Particularly, the inhibitory effect of3 was equivalent to aspirin. Abstract :